2020
DOI: 10.1001/jamahealthforum.2020.0426
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Leading Health Indicators for Healthy People 2030

Abstract: Services (DHHS), has set health promotion and disease prevention objectives and targets every decade in an effort to engage a broad constituency in achieving health gains for the nation. A subset of objectives-the Leading Health Indicators (LHIs)-are intended to sharply focus attention on the highest priorities. At the request of DHHS, the National Academies of Sciences, Engineering, and Medicine appointed a committee in 2019, on which we served and which 1 of us staffed. The committee was charged with informi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…13 These efforts, in addition to addressing SDH, are critical to reduce new HIV infections consistent with the goals of Healthy People 2030 and the Ending the HIV Epidemic initiative. 12,13,42,43…”
Section: Discussionmentioning
confidence: 99%
“…13 These efforts, in addition to addressing SDH, are critical to reduce new HIV infections consistent with the goals of Healthy People 2030 and the Ending the HIV Epidemic initiative. 12,13,42,43…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have identified racial and ethnic disparities in the management and treatment of acute coronary syndromes (ACS) and have consistently demonstrated that individuals of Black race are less likely than White individuals to receive invasive cardiac procedures such as coronary angiography and percutaneous cutaneous intervention (PCI). 1 , 2 , 3 , 4 , 5 , 6 Professional societies such as the American Heart Association 7 and Centers for Disease Control and Prevention's Healthy People 2030 8 , 9 have asserted that addressing racial disparities is a priority. 4 , 10 , 11 Identifying the extent of differences in ACS treatment by race and ethnicity in contemporary data is essential for documenting progress toward their resolution.…”
mentioning
confidence: 99%
“…Similarly, 70% of the case scenarios had triggers addressing one or more social determinants of health. Improving our understanding social determinants of health such as environments in which people are born, grow, live, work and age, factors such as socioeconomic status, education, employment, and access to health care is critical to provide targeted healthcare and in shaping people's health [16][17][18] A majority of the PBL case scenarios (87%) re ected contextual integration of medical professionalism, evolving roles of doctors in health system (79%) and re ected healthcare referral system based on the case complexity (73%). We believe these traits are critical in providing good clinical care, maintaining good medical practice, relationships with patients, working with colleagues, probity, and health [19].…”
Section: Discussionmentioning
confidence: 99%